Hydrothermal liquefaction of macro algae: Effect of feedstock composition. (15th April 2015) - Singh, Rawel; Balagurumurthy, Bhavya; Bhaskar, Thallada
Highlights: Hydrothermal liquefaction of three macro algae samples was performed. Compositional variations of macro algae were reflected in bio-oil & bio-residue yields. Maximum conversion and bio-oil (81% and 12%) was observed with macro algae UF. High percentage of aliphatic functional groups was observed in all bio-oils. Abstract: Due to the increasing thrust on third generation biofuels, algal research has gained a lot of importance in the recent years. Effective utilization of algal biomass in a single step is necessary as it can produce fungible hydrocarbons in addition to a variety of valuable products. Hydrothermal liquefaction does not require the energy intensive drying steps and is an attractive approach for the conversion of algae which has high moisture content. The objective of this study is to understand the effect of compositional changes of macro algae samples Ulva fasciata (MA'UF), Enteromorpha sp. (MA'E) and Sargassum tenerrimum (MA'ST) on product distribution and nature of products. Various macro algae samples were converted to bio-oil by hydrothermal liquefaction in a batch reactor at 280 °C for 15 min with biomass:water ratio of 1:6. The liquefaction products were separated into ether soluble fraction (bio-oil1), water-soluble fraction, solid residue and gaseous fraction. Maximum conversion of 81% was observed with macro algae (MA) UF. The effect of varying feedstock compositions were reflected in the bio-oil and bio-residue yields. The maximum conversion and bio-oil yield was observed with MA'UF due to the presence of higher carbohydrate content than other feeds. FTIR and NMR spectra showed high percentage of aliphatic functional groups for all bio-oils.